If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10=7y+3(y-6)
We move all terms to the left:
10-(7y+3(y-6))=0
We calculate terms in parentheses: -(7y+3(y-6)), so:We get rid of parentheses
7y+3(y-6)
We multiply parentheses
7y+3y-18
We add all the numbers together, and all the variables
10y-18
Back to the equation:
-(10y-18)
-10y+18+10=0
We add all the numbers together, and all the variables
-10y+28=0
We move all terms containing y to the left, all other terms to the right
-10y=-28
y=-28/-10
y=2+4/5
| x/5=6=16 | | y/4-20=12 | | 9b+14=11b | | -5v-5=2(v+1) | | x+15=-11 | | 12=4+b | | 193+c=234 | | 4x3=1 | | 4p-3p=11 | | 5x–3=2x+27 | | -3(x-6)=-5x+31 | | 17j-11j=12 | | F(-5)=-7x-5 | | -9+2x-x=-8 | | 5p+17=1495 | | 4(z-2)4z=-13 | | 6i+8i=0 | | 4t+3=6+2t | | 2y(y-3)=27+y^2 | | -2(-3x+1)=-14 | | 6+7x=8+2 | | 2x+4-x=4x+5 | | 2y(y-3)=27+y2 | | x/12=44 | | F(-5)=-0.25x-6 | | x+(-x)=x+3 | | F(-2.25)=-0.25x-6 | | 5x+8x=112 | | 9x−13=4x+32 | | -4n-8=4(-3n-2) | | 4+5=7+3x | | 6x+12+30=90 |